Exploring the buffer effect of receiving social support on lonely and emotionally unstable social networking users. (January 2019) - Lo, Janice
Abstract: Although much research has been conducted to explain the stresses related to the use of social networking sites (SNSs), it remains unclear how this stress from SNS-related activities can be alleviated, especially for users who are associated with problematic use of SNS, namely lonely and emotionally unstable users. This paper draws from the field of medicine the buffer effect of social support theory to postulate that receiving social support online is a potential deterrent of exhaustion and a promoter of user satisfaction. The study depicts the role of receiving social support in a context involving social overload, exhaustion, satisfaction, and the intention to discontinue using a SNS. Based on a sample of 1285 Facebook users, it is found that receiving social support in general helps ease the exhaustion users feel from their SNS use and improves their SNS satisfaction. However, despite the positive effect of receiving social support, SNS use does not provide the same level of benefit to everyone and appears to be a greater source of stress for lonely and emotionally unstable users. Highlights: Receiving social support online in general helps ease social networking exhaustion. Neurotic users receive more social support online than others. Receiving social support does not reduce exhaustion for neurotic users. Social networking use is a greater source of stress for lonely and neurotic users. Lonely users experience higher social overload, higher social networking exhaustion.